Utilizing realistic assessment strategies and tools in the assessment of students of the upper elementary stage in public schools in Zarqa I - Jordan - Al Najjar, Yousry Abdel Rahim Yousef (Journal of Educational and Psychological Sciences, 2018)
The objective of this research is to investigate the extent to which teachers and teachers are employed for real-life evaluation strategies and tools in the public schools of Zarqa I, Jordan. The research used the survey method and quantitative qualitative analytical research method. A questionnaire was distributed to a sample of 100 teachers from various disciplines. The results of the study showed that the degree of teachers' reliance on the realistic assessment strategies based on communication (questions and answers), observation (automatic), paper and pen (multiple choice) and self assessment were the highest among the teachers with average (4.55) (5). As for the evaluation tools, the monitoring lists topped the highest (4.99), followed by the digital estimation scales (4.41). The results of the study showed that there were no statistically significant differences due to gender, specialization or years of service. There were statistically significant differences due to the variable receiving training courses for realistic evaluation strategies. In light of the results, a number of recommendations were recommended to improve the evaluation of the basic stage students in Jordan.
Keywords: evaluation; evaluation strategies; evaluation tools; realistic evaluation; educational evaluation